PERSEPSI TERHADAP WISATA HALAL DI KOTA PADANG - Sri Maryati (Universitas Islam Negeri Imam Bonjol Padang, 2019)
Halal tourism is tourism that puts forward the values and norms of Islamic Sharia as a basic foundation. As a new concept in the tourism industry, halal tourism requires efforts and development strategies as well as a comprehensive understanding of how to accommodate Islamic values in tourism activities. This study aims to see how the perception of tourist visitors in the city of Padang, one of the National Priority Halal destinations. This research is a descriptive study with a survey method conducted on 100 respondents chosen randomly in Padang destinations and tourist attractions. The halal tourism dimension is adapted from indicators applied by the Global Muslim Travel Index (GMTI).